Globalisation of the World Economy - Pros and Cons - Miškinis, Algirdas (Ekonomika, 2002)
The article deals with the globalisation process in general and its implications for developing and transition countries. Globalisation is understood as a growing interdependance of world economy, as an economic integration of different countries through an international trade, the movement of capital, an increasing role of transnational corporations, a technological change. The current globalisation is not a new phenomenon. The world underwent a globalisation process one hundred years ago which according to most indicators was much deeper. The globalisation in principal changed comparative advantages of countries. The endowment of factors of production becomes less important than an education level, new materials and technologies, the developed economic and social infrastructure. It is therefore very important to develop economic economic policies that stimulate development of these factors. Article emphasizes the role of transnational corporations in current globalisation process. The economic development of both developing and transition economies to large extent depend on their capabilities to attract investments of transnational corporations. As not each foreign investment are equally beneficial it is important to establish a promotion system to attract productive investment in most perspective sectors and first of all to those producing high value added. It is also important to promote the access of domestic companies to production systems and distribution networks controlled by transnational corporations. Globalisation is supported by regionalisation which is, however, sometimes is in conflict with global trade liberalization. Regionlisation as well as globalisation is not equally advantageous to all member countries. Usually more developed country reaps more benefits from trade block than less developed. In such circumstances it is important to develop policies assisting domestic companies in export development The article assesses the level of intergration of transition economies into world economic system. It argues that trade liberalization is not the main determinant of economic growth, vice versa it can have a negative impact due to cyclical fluctuations of world prices which is the case also for exports from transitional economies. The corresponding policy measures should be developed to mitigate the negative outcomes of trade openness.